Aluminum alloy wire and preparation method thereof

By controlling the content range of elements in aluminum alloy wires and adopting surface treatment technology, the problems of dullness and roughness of the surface of aluminum alloy wires are solved, and bright surfaces, excellent surface quality and good corrosion resistance are achieved.

CN119571152BActive Publication Date: 2025-04-18CHINALCO MATERIALS APPL RES INST CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510132595.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-06
Publication Date
2025-04-18
Estimated Expiration
2045-02-06

AI Technical Summary

Technical Problem

The finished aluminum alloy wire products have problems such as dull surface color, poor finish and residual drawing marks, resulting in unqualified finished products and poor aesthetics of fasteners.

Method used

By controlling the content range of Zn, Mg, Cu, Mn, Fe and Si elements in the aluminum alloy wire, and using surface dissolution, alkali corrosion, pickling, water washing and coating processes, uniform tissue structure and good surface characteristics are formed.

Benefits of technology

The bright surface, excellent surface quality and good corrosion resistance of the aluminum alloy wire are achieved, avoiding the adverse effects of additional coatings and subsequent processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571152B_ABST
    Figure CN119571152B_ABST
Patent Text Reader

Abstract

The present invention provides an aluminum alloy wire and a preparation method thereof. The aluminum alloy wire comprises the following elements by mass percentage: 0.1-7.0% of Zn element, 0.2-9.6% of Mg element, 0.1-6.0% of Cu element, 0.01-1.2% of Mn element, 0.1-2.0% of Fe element and 0.1-2.5% of Si element, the total content of inevitable impurities is ≤0.15%, and the balance is Al element; the surface brightness L of the aluminum alloy wire is greater than 60, and the surface brightness color difference △E is ≤0.5; the average roughness Sa is ≤0.4μm, and the maximum peak height Sp is ≤2.0μm; the aluminum alloy wire does not crack after 85% compression deformation; at a temperature of 35°C, placed in a 57g / L NaCl solution and a 10mL / L H 2 O 2 Under the test conditions of immersion in the mixed solution of the solution for 6 hours, the corrosion depth of the aluminum alloy wire is ≤10μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum alloys, and in particular to an aluminum alloy wire and a preparation method thereof. Background Art

[0002] At present, most aerospace mainframe assemblies use steel and titanium rivets. Due to the increasingly higher requirements for the flight speed and mounting of aerospace vehicles, aluminum alloys have become the preferred material to replace steel and titanium fasteners due to their light weight and high strength.

[0003] Aluminum alloy wire rod is the raw material for the preparation of aluminum alloy fasteners. Affected by the production process control, the current aluminum alloy wire finished products have surface quality problems such as dull surface color and scratches left along the deformation direction. The scratch marks can easily become the source of cracks, leading to forming cracks, and the aesthetics of the fastener parts is also poor.

[0004] In order to deal with the surface quality problem of aluminum alloy wires, methods such as scraping the finished product and spraying a protective layer are generally used. Among them, the scraping method is to scrape the surface of the finished wire to remove the residual black oxide scale or scratches, but the scraper will cause additional damage to the surface of the wire, resulting in a rough and uneven surface, which will reduce the surface quality and corrosion resistance of the material. Although a layer of aluminum alloy surface protective layer is formed by surface spraying, it can temporarily play a surface protection role, but once the protective layer is broken, it will form a micro-area electrochemical corrosion coupling with the aluminum matrix, which will accelerate surface erosion. At the same time, the surface spray protection of the wire will also have a chemical interaction effect on other surface protection (such as anodizing, painting and coatings) after the subsequent preparation of fastener parts.

[0005] As OEMs further improve their requirements for riveting performance, there are more and more scenarios where the compression performance of aluminum alloy wires used for fasteners is required to be greater than 80%. However, existing aluminum alloy wires used for fasteners have many cracking problems, resulting in unqualified products that cannot be delivered. Therefore, it is urgent to develop surface improvement technology for aluminum alloy wire intermediate processes. Summary of the invention

[0006] The main purpose of the present invention is to provide an aluminum alloy wire and a preparation method thereof, so as to solve the problems of dark surface color, poor finish and residual drawing marks in the finished aluminum alloy wire in the prior art.

[0007] To achieve the above-mentioned object, according to one aspect of the present invention, there is provided an aluminum alloy wire, which comprises the following elements, in percentage by mass: 0.1-7.0% of Zn element, 0.2-9.6% of Mg element, 0.1-6.0% of Cu element, 0.01-1.2% of Mn element, 0.1-2.0% of Fe element and 0.1-2.5% of Si element, the total content of inevitable impurities is ≤0.15%, and the balance is Al element; the surface brightness L of the aluminum alloy wire is greater than 60, and the surface brightness color difference △E of the aluminum alloy wire is ≤0.5; the average roughness Sa of the aluminum alloy wire is ≤0.4μm, and the maximum peak height Sp of the aluminum alloy wire is ≤2.0μm; the aluminum alloy wire does not crack after 85% compression deformation; under the test conditions of immersion in a mixed solution of 57g / L NaCl solution and 10mL / L H2O2 solution for 6h at a temperature of 35°C, the corrosion depth of the aluminum alloy wire is ≤10μm.

[0008] Furthermore, the aluminum alloy wire comprises the following elements, in percentage by mass: 0.5-5.5% of Zn, 0.5-6.0% of Mg, 0.5-5.0% of Cu, 0.01-0.8% of Mn, 0.1-1.5% of Fe and 0.1-2.0% of Si, the total content of unavoidable impurities is ≤0.15%, and the balance is Al; and / or the mass ratio of Fe to Cu is 0.02-3:1, and / or the mass ratio of Mn to Cu is 0.1-1.6:1.

[0009] Furthermore, the recrystallized texture content of the aluminum alloy wire is 60-95%, and / or the dislocation density of the aluminum alloy wire is 0.2×10 14 ~1.0×10 14 m -2 , and / or, the average grain size of the aluminum alloy wire is 5~350μm.

[0010] According to another aspect of the present invention, there is provided a method for preparing the above-mentioned aluminum alloy wire, the preparation method comprising: step S1, subjecting the raw materials corresponding to the aluminum alloy to batching, smelting, casting, homogenization treatment, hot rough rolling and hot finish rolling in sequence to obtain a hot-rolled billet; step S2, subjecting the hot-rolled billet to surface dissolution, alkali etching, pickling, water washing and coating in sequence to obtain a coated billet; step S3, subjecting the coated billet to intermediate annealing and cold drawing in sequence to obtain a cold-drawn wire; and step S4, repeating the treatment process of step S2 and step S3 on the cold-drawn wire to obtain an aluminum alloy wire; wherein the electrode potential of the hot-rolled billet is -770~-1600mV; and the temperature of the intermediate annealing is 400~550℃.

[0011] Furthermore, in the above step S2, the process of surface dissolution includes: performing a first spraying on the hot-rolled billet with a surface dissolving agent to obtain a billet after surface dissolution; wherein the surface dissolving agent includes 5~15wt% of a degreasing agent, 2~15wt% of an activating agent and 8~12wt% of a penetrant; and / or, the temperature of the first spraying is 60~90°C, and / or, the pressure of the first spraying is 10~18MPa; and / or, the time of the first spraying is 5~15s.

[0012] Furthermore, the degreasing agent is selected from any one or more of boric acid, aminosulfonic acid, borates, sulfates and carbonates, and / or the activating agent is selected from any one or more of alkylphenol polyoxyethylene ether, isomeric decanol polyethylene ether, hexadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide and fatty alcohol polyoxyethylene ether; and / or the penetrant is selected from any one or more of dipropylene glycol, fatty alcohol polyoxyethylene ether and sodium alkyl sulfonate.

[0013] Furthermore, in the above step S2, the alkaline etching process includes: using an alkaline etching agent to perform a second spraying on the blank after surface dissolution to obtain an alkaline-etched blank; wherein the alkaline etching agent includes 3~10wt% of sodium hydroxide, 6~10wt% of sodium carbonate and 2~8wt% of sodium nitrate; and / or, the temperature of the second spraying is 60~90°C, and / or, the pressure of the second spraying is 1~10MPa; and / or, the time of the second spraying is 13~25s.

[0014] Further, in the above step S2, the pickling process includes: using a pickling agent to perform a third spray on the alkaline-etched blank to obtain a pickled blank; wherein the pickling agent includes 2~6wt% hydrofluoric acid, 2~10wt% phosphoric acid, 1~3wt% nitric acid, 1~2wt% sulfuric acid and 3~16wt% organic acid; wherein the organic acid is selected from any one or more of tartaric acid, malonic acid, oxalic acid, malic acid and citric acid; and / or, the temperature of the third spraying is 70~90°C, and / or, the pressure of the third spraying is 1~5MPa; and / or, the time of the third spraying is 15~20s.

[0015] Furthermore, in the above-mentioned step S2, the coating process includes: using the coating liquid to perform a fourth spraying on the washed blank to obtain a coated blank; wherein the coating liquid includes 7~18wt% of an extender, 9~12wt% of a regulator, and 0.5~2wt% of a corrosion inhibitor; and / or, the temperature of the fourth spraying is 60~90°C, and / or, the pressure of the fourth spraying is 1~8MPa; and / or, the time of the fourth spraying is 15~20s.

[0016] Furthermore, the supplementer is selected from any one or more of fluoroboric acid, ethanol, boric acid and phosphoric acid; and / or the adjuster is selected from any one or more of nitric acid, hydrofluoric acid and phosphate; and / or the corrosion inhibitor is selected from any one or more of hexamethylenetetramine, potassium nitrite, sodium gluconate, nitrilotrimethylenephosphonic acid, ethanolamine phosphate and hexadecylamine.

[0017] By applying the technical solution of the present invention, the present application can avoid the excessive formation of large-sized second phases such as AlCuFe and AlCuMn by controlling the content of each element within the above range, especially the control of Fe, Mn and Cu elements, which is conducive to the reasonable regulation of the electrode potential of the alloy surface layer, thereby making the aluminum alloy wire uniform in structure and having good surface brightness and surface roughness and other properties. At the same time, under the above-mentioned corrosion test conditions, the corrosion depth of the aluminum alloy wire reaches the above-mentioned range. Therefore, the aluminum alloy wire of the present application also has good corrosion resistance. In summary, the aluminum alloy wire of the present application presents a bright surface, the surface quality of the finished product is excellent, there is no additional coating, and there is no adverse effect on the processing of rear-end fastener parts. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0019] Figure 1 The surface morphology of the aluminum alloy wire in Example 1 of the present application is shown;

[0020] Figure 2 The surface roughness diagram of the aluminum alloy wire in Example 1 of the present application is shown;

[0021] Figure 3 The corrosion morphology of the aluminum alloy wire in Example 1 of the present application is shown;

[0022] Figure 4 The surface morphology of the aluminum alloy wire in Comparative Example 5 of the present application is shown;

[0023] Figure 5 The surface roughness diagram of the aluminum alloy wire in Comparative Example 5 of the present application is shown;

[0024] Figure 6 The corrosion morphology of the aluminum alloy wire in Comparative Example 5 of the present application is shown;

[0025] Figure 7 A flow chart of the method for preparing aluminum alloy wire in Example 1 of the present application is shown. DETAILED DESCRIPTION

[0026] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0027] As analyzed in the background technology of this application, the finished aluminum alloy wire in the prior art has the problems of dark surface color, poor finish and residual drawing marks. In order to solve the above problems, this application provides an aluminum alloy wire and a preparation method thereof.

[0028] In a typical embodiment of the present application, an aluminum alloy wire is provided, which includes the following elements, by mass percentage: 0.1-7.0% of Zn element, 0.2-9.6% of Mg element, 0.1-6.0% of Cu element, 0.01-1.2% of Mn element, 0.1-2.0% of Fe element and 0.1-2.5% of Si element, the total content of inevitable impurities is ≤0.15%, and the balance is Al element; the surface brightness L of the aluminum alloy wire is greater than 60, and the surface brightness color difference △E of the aluminum alloy wire is ≤0.5; the average roughness Sa of the aluminum alloy wire is ≤0.4μm, and the maximum peak height Sp of the aluminum alloy wire is ≤2.0μm; the aluminum alloy wire does not crack after 85% compression deformation; under the test conditions of immersion in a mixed solution of 57g / L NaCl solution and 10mL / L H2O2 solution for 6h at a temperature of 35°C, the corrosion depth of the aluminum alloy wire is ≤10μm.

[0029] The present application can avoid the excessive formation of large-sized second phases such as AlCuFe and AlCuMn by controlling the content of each element within the above range, especially the control of Fe, Mn and Cu elements, which is conducive to the reasonable regulation of the electrode potential of the alloy surface layer, thereby making the aluminum alloy wire uniform in structure and having good surface brightness and surface roughness and other properties. At the same time, under the above corrosion test conditions, the corrosion depth of the aluminum alloy wire reaches the above range, so the aluminum alloy wire of the present application also has good corrosion resistance. In summary, the aluminum alloy wire of the present application presents a bright surface, the finished product has excellent surface quality, no additional coating, and no adverse effects on the processing of rear-end fastener parts.

[0030] The maximum peak height Sp is the maximum height of the surface peak and is a parameter of surface roughness.

[0031] In order to further improve the surface brightness and surface quality of the aluminum alloy wire, in one embodiment of the present application, the aluminum alloy wire includes the following elements, by mass percentage: 0.5-5.5% of Zn element, 0.5-6.0% of Mg element, 0.5-5.0% of Cu element, 0.01-0.8% of Mn element, 0.1-1.5% of Fe element and 0.1-2.0% of Si element, the total content of unavoidable impurities is ≤0.15%, and the balance is Al element; and / or, the mass ratio of Fe element to Cu element is 0.02-3:1, and / or, the mass ratio of Mn element to Cu element is 0.1-1.6:1.

[0032] The mass ratio of the Fe element to the Cu element is preferably within the above range, which is beneficial to avoid the generation of large-sized AlCuFe phases. The mass ratio of the Mn element to the Cu element is preferably within the above range, which helps to avoid the generation of large-sized AlCuMn phases. Since the electrode potentials of the AlFeMn and AlCuMn phases are -550mV and -560mV respectively, which deviate too much from the Al matrix -770mV, and their size is large, the Al matrix around them is induced to form spontaneous corrosion, which is easy to fall off after alkaline etching and pickling to form pit defects. Therefore, it is preferred that the mass ratio of the Fe element to the Cu element and the mass ratio of the Mn element to the Cu element are within the above range, which helps to form a film on the surface of the aluminum alloy wire, thereby improving its surface quality.

[0033] In one embodiment of the present application, the recrystallized texture content of the aluminum alloy wire is 60-95%, and / or the dislocation density of the aluminum alloy wire is 0.2×10 14 ~1.0×10 14 m -2 , and / or, the average grain size of the aluminum alloy wire is 5~350μm.

[0034] It is preferred to control the recrystallization texture content, dislocation density and average grain size of the modified aluminum alloy wire within the above ranges, which helps to form a sufficient recrystallization structure and a lower dislocation density, thereby further improving the density of the product film on the surface of the aluminum alloy wire after corrosion, and further improving the corrosion resistance and wear resistance of the aluminum alloy wire.

[0035] In a typical embodiment of the present application, a method for preparing the above-mentioned aluminum alloy wire is provided, and the preparation method comprises: step S1, sequentially performing batching, smelting, casting, homogenization treatment, hot rough rolling and hot finish rolling on the raw materials corresponding to the aluminum alloy to obtain a hot-rolled billet; step S2, sequentially performing surface dissolution, alkaline etching, pickling, water washing and coating on the hot-rolled billet to obtain a coated billet; step S3, sequentially performing intermediate annealing and cold drawing on the coated billet to obtain a cold-drawn wire; and step S4, repeating the treatment process of step S2 and step S3 on the cold-drawn wire to obtain an aluminum alloy wire; wherein the electrode potential of the billet is -770~-1600mV; and the temperature of the intermediate annealing is 400~550℃.

[0036] The present application adopts surface dissolution, alkaline etching, pickling, water washing and coating treatment processes for the wire billet before each annealing pass, which can fully remove the residual oil on the surface of the wire after cold drawing, and cover a layer of protective film layer, thereby preventing the aluminum alloy wire from generating mutual contact corrosion and environmental medium corrosion during storage and parking, while avoiding the darkening caused by carbonization and penetration of cold drawing oil into the surface of the aluminum alloy wire during annealing, and also avoiding the carbide residue in the pores of the drawing die causing drawing scratches that affect the surface quality and forming yield of the aluminum alloy wire. Among them, the present application controls the electrode potential of the hot-rolled billet within the above range (with the calomel electrode as the reference electrode), effectively avoiding the problem that the exposed surface has poor corrosion resistance due to the presence of a large number of large-sized second phase particles with a large potential difference with the aluminum matrix in the hot-rolled billet, which is not conducive to the uniformity of subsequent alkaline etching, pickling and coating. Repeating the processing of step S2 and step S3 on the cold-drawn wire until the product diameter specification requirements (diameter is 1.0~15mm) are met can ensure that the cold-drawn wire is protected on the surface in each pass of the treatment, avoiding damage to the surface of the wire in the intermediate pass, thereby ensuring the surface quality of the finished aluminum alloy wire. The temperature of the intermediate annealing is preferably within the above range, which can fully soften the cold-drawn wire in preparation for the next drawing while vaporizing the covered film layer, avoiding the film layer from affecting the next cold drawing or the final aluminum alloy wire product. The aluminum alloy wire obtained by the preparation method of the present application has excellent surface quality and forming performance and other properties.

[0037] In one embodiment of the present application, in the above-mentioned step S2, the process of surface dissolution includes: using a surface dissolving agent to perform a first spraying on the hot-rolled billet to obtain a billet after surface dissolution; wherein the surface dissolving agent includes 5~15wt% of a degreasing agent, 2~15wt% of an activator and 8~12wt% of a penetrant; and / or, the temperature of the first spraying is 60~90°C, and / or, the pressure of the first spraying is 10~18MPa; and / or, the time of the first spraying is 5~15s.

[0038] The surface dissolving agent is preferably used to dissolve the hot-rolled billet surface, which helps to remove residual grease on the surface of the hot-rolled billet. Specifically, the activating agent and the degreasing agent help to further promote the decomposition and separation of residual grease on the billet surface after the surface dissolution, and the penetrant helps to accelerate the penetration speed of the surface dissolving agent, thereby helping to quickly separate and remove the surface grease from the aluminum alloy matrix within the time of the first spraying, thereby achieving a surface purification effect.

[0039] In order to further improve the surface purification effect, in one embodiment of the present application, the degreasing agent is selected from any one or more of boric acid, aminosulfonic acid, borates, sulfates and carbonates, and / or the active agent is selected from any one or more of alkylphenol polyoxyethylene ether, isomeric decanol polyethylene ether, hexadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide and fatty alcohol polyoxyethylene ether; and / or the penetrant is selected from any one or more of dipropylene glycol, fatty alcohol polyoxyethylene ether and sodium alkyl sulfonate.

[0040] In one embodiment of the present application, in the above-mentioned step S2, the alkaline etching process includes: using an alkaline etching agent to perform a second spraying on the blank after surface dissolution to obtain an alkaline-etched blank; wherein the alkaline etching agent includes 3~10wt% of sodium hydroxide, 6~10wt% of sodium carbonate and 2~8wt% of sodium nitrate; and / or, the temperature of the second spraying is 60~90°C, and / or, the pressure of the second spraying is 1~10MPa; and / or, the time of the second spraying is 13~25s.

[0041] Adopting the above-mentioned alkaline etching process and further optimizing the formula of the alkaline etching agent can help provide an alkaline environment to slightly alkali-etch the micron layer on the surface of the blank after the surface is dissolved, creating a surface environment with a certain degree of roughness in the micro-region, which is beneficial to the subsequent coating layer.

[0042] In one embodiment of the present application, in the above-mentioned step S2, the pickling process includes: using a pickling agent to perform a third spray on the alkaline-etched blank to obtain a pickled blank; wherein the pickling agent includes 2~6wt% hydrofluoric acid, 2~10wt% phosphoric acid, 1~3wt% nitric acid, 1~2wt% sulfuric acid, and 3~16wt% organic acid; wherein the organic acid is selected from any one or more of tartaric acid, malonic acid, oxalic acid, malic acid and citric acid; and / or, the temperature of the third spraying is 70~90°C, and / or, the pressure of the third spraying is 1~5MPa; and / or, the time of the third spraying is 15~20s.

[0043] The above pickling process and further optimization of the pickling agent formula are helpful to neutralize and clean the residual alkali solution after the alkaline etching process, and soften the micro-area surface of the blank after alkaline etching, thereby reducing the excessive surface roughening caused by alkaline etching. Once excessive roughening occurs, the next coating layer will not be able to completely cover the surface of the blank, exposing the original substrate and causing damage or corrosion. Therefore, the above pickling process is helpful to reduce the excessive surface roughening caused by alkaline etching, which is conducive to the coating layer covering the surface of the blank.

[0044] In one embodiment of the present application, in the above-mentioned step S2, the coating process includes: using a coating liquid to perform a fourth spraying on the washed blank to obtain a coated blank; wherein the coating liquid includes 7~18wt% of an extender, 9~12wt% of a regulator, and 0.5~2wt% of a corrosion inhibitor; and / or, the temperature of the fourth spraying is 60~90°C, and / or, the pressure of the fourth spraying is 1~8MPa; and / or, the time of the fourth spraying is 15~20s.

[0045] By adopting the above-mentioned coating process, a micron-level film layer suitable for the surface of aluminum alloy is provided, which has a high hardness, so as to protect the surface of the billet after alkali etching and pickling, thereby reducing the influence of corrosion and scratches on the forming performance of aluminum alloy wire during storage, parking and transportation. At the same time, adding 0.5-2% corrosion inhibitor to the coating liquid helps aluminum alloy to alleviate the excessive growth of the film layer, which is conducive to the complete decomposition of the film layer above 400°C, and then helps the wire after cold drawing to directly vaporize and detach from the surface of the aluminum alloy wire during the last annealing process at 400-550°C, so that the surface of the aluminum alloy wire has no black matter residue, the surface is bright, the quality is excellent, and the corrosion resistance is greatly improved.

[0046] In order to further improve the surface quality and corrosion resistance of the aluminum alloy wire, in one embodiment of the present application, the supplementer is selected from any one or more of fluoroboric acid, ethanol, boric acid and phosphoric acid; and / or the regulator is selected from any one or more of nitric acid, hydrofluoric acid and phosphate; and / or the corrosion inhibitor is selected from any one or more of hexamethylenetetramine, potassium nitrite, sodium gluconate, nitrilotrimethylenephosphonic acid, ethanolamine phosphate and hexadecylamine.

[0047] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0048] Example 1

[0049] Step S1, the aluminum alloy raw material is prepared according to the components of 7.0% Zn element, 0.2% Mg element, 0.5% Cu element, 0.01% Mn element, 1.5% Fe element and 0.1% Si element and the balance of Al element, and then smelting, casting, homogenization treatment, hot rough rolling and hot finish rolling are carried out in sequence to obtain a hot-rolled billet, and the electrode potential of the hot-rolled billet is -770mV.

[0050] Step S2, the hot-rolled billet is subjected to surface dissolution, alkaline etching, pickling, water washing and coating in sequence to obtain a coated billet. The surface dissolution process is as follows: the billet is first sprayed at 60°C for 5s with a surface dissolving agent, and the pressure of the first spraying is 10MPa to obtain a billet after surface dissolution. The surface dissolving agent is a mixed solution containing 5wt% of a degreasing agent (aminosulfonic acid, borate and sulfate), 2wt% of an active agent (alkylphenol polyoxyethylene ether, isomeric decanol polyethylene ether and hexadecyl trimethyl ammonium chloride) and 8wt% of a penetrant (dipropylene glycol and fatty alcohol polyoxyethylene ether).

[0051] The alkaline etching process is to use an alkaline etching agent to dissolve the surface of the blank and then perform a second spraying at 60°C for 13 seconds. The pressure of the second spraying is 1 MPa to obtain an alkaline-etched blank. The alkaline etching agent is a mixed solution containing 3wt% sodium hydroxide, 6wt% sodium carbonate and 2wt% sodium nitrate.

[0052] The pickling process is to use a pickling agent to perform a third spraying of the alkaline-etched blank at 70°C for 15 seconds, and the pressure of the third spraying is 1MPa to obtain the pickled blank. The pickling agent is a mixed solution containing 2wt% hydrofluoric acid, 2wt% phosphoric acid, 1wt% nitric acid, 1wt% sulfuric acid, and 3wt% organic acid malonic acid.

[0053] The coating process is to use the coating liquid to spray the washed blank for the fourth time at 60°C for 20s, and the pressure of the fourth spray is 1MPa to obtain the coated blank. The coating liquid is a mixed liquid containing 7wt% of supplements (fluoroboric acid, anhydrous ethanol and boric acid), 9wt% of regulators (nitric acid and hydrofluoric acid), and 0.5wt% of corrosion inhibitors (potassium nitrite, sodium gluconate, nitrilotrimethylenephosphonic acid, ethanolamine phosphate).

[0054] Step S3, subjecting the coated blank to intermediate annealing at 400° C. and then cold drawing to obtain a cold drawn wire.

[0055] Step S4, repeating the processing of steps S2 and S3 on the cold drawn wire until it is drawn to a specification of φ3.2 mm, thereby obtaining an aluminum alloy wire.

[0056] The preparation method flow chart of the above aluminum alloy wire is as follows Figure 7 shown.

[0057] Example 2

[0058] Step S1, the aluminum alloy raw material is prepared according to the components of 0.5% Zn element, 6.0% Mg element, 0.5% Cu element, 0.8% Mn element, 0.1% Fe element and 2.0% Si element, and the balance is Al element, and then smelting, casting, homogenization treatment, hot rough rolling and hot finishing rolling are carried out in sequence to obtain a hot-rolled billet, and the electrode potential of the hot-rolled billet is -1600mV.

[0059] Step S2, the hot-rolled billet is subjected to surface dissolution, alkaline etching, pickling, water washing and coating in sequence to obtain a coated billet. The surface dissolution process is as follows: the billet is first sprayed at 90°C for 15s with a surface dissolving agent, and the pressure of the first spraying is 18MPa to obtain a billet after surface dissolution. The surface dissolving agent is a mixed solution containing 15wt% of a degreasing agent (boric acid, aminosulfonic acid and carbonate), 15wt% of an activator (hexadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide and fatty alcohol polyoxyethylene ether) and 12wt% of a penetrant (dipropylene glycol, fatty alcohol polyoxyethylene ether and sodium alkyl sulfonate).

[0060] The alkaline etching process is to use an alkaline etching agent to dissolve the surface of the blank and then perform a second spraying at 90°C for 25 seconds. The pressure of the second spraying is 10 MPa to obtain an alkaline-etched blank. The alkaline etching agent is a mixed solution containing 10wt% sodium hydroxide, 10wt% sodium carbonate and 8wt% sodium nitrate.

[0061] The pickling process is to use a pickling agent to perform a third spraying of the alkaline-etched blank at 90°C for 20 seconds, and the pressure of the third spraying is 5MPa to obtain the pickled blank. The pickling agent is a mixed solution containing 6wt% hydrofluoric acid, 10wt% phosphoric acid, 3wt% nitric acid, 2wt% sulfuric acid, and 16wt% organic acid malonic acid.

[0062] The coating process is to use the coating liquid to spray the washed blank for the fourth time at 60°C for 20 seconds, and the pressure of the fourth spraying is 8MPa to obtain the coated blank. The coating liquid is a mixed liquid containing 18wt% of supplements (fluoroboric acid, anhydrous ethanol and boric acid), 12wt% of regulators (nitric acid and hydrofluoric acid), and 2wt% of corrosion inhibitors (nitrilotrimethylenephosphonic acid, ethanolamine phosphate, and hexadecylamine).

[0063] Step S3, subjecting the coated blank to intermediate annealing at 550° C. and then cold drawing to obtain a cold drawn wire.

[0064] Step S4, repeating the processing of steps S2 and S3 on the cold drawn wire until it is drawn to a specification of φ5.5 mm, thereby obtaining an aluminum alloy wire.

[0065] Example 3

[0066] The difference from Example 1 is that the process of surface dissolution is: the hot rolled billet is first sprayed with a surface dissolving agent at 70°C for 7s, and the pressure of the first spraying is 11MPa to obtain a billet after surface dissolution. The surface dissolving agent is a mixed solution containing 8wt% of a degreasing agent, 6wt% of an activating agent and 9wt% of a penetrant, and finally an aluminum alloy wire is obtained.

[0067] Example 4

[0068] The difference from Example 1 is that the process of surface dissolution is: the hot rolled billet is first sprayed with a surface dissolving agent at 50°C for 20s, and the pressure of the first spraying is 20MPa to obtain a billet after surface dissolution. The surface dissolving agent is a mixed solution containing 2wt% of a degreasing agent, 18wt% of an activating agent and 3wt% of a penetrant, and finally an aluminum alloy wire is obtained.

[0069] Example 5

[0070] The difference from Example 1 is that the alkaline etching process is to use an alkaline etching agent to dissolve the surface of the billet and then perform a second spraying at 65° C. for 18 seconds. The pressure of the second spraying is 7 MPa to obtain an alkaline-etched billet. The alkaline etching agent is a mixed solution containing 6wt% of sodium hydroxide, 8wt% of sodium carbonate and 3wt% of sodium nitrate, and finally obtain an aluminum alloy wire.

[0071] Example 6

[0072] The difference from Example 1 is that the alkaline etching process is to use an alkaline etching agent to dissolve the surface of the billet and then perform a second spraying at 50°C for 10 seconds, and the pressure of the second spraying is 12MPa to obtain an alkaline-etched billet. The alkaline etching agent is a mixed solution containing 2wt% sodium hydroxide, 5wt% sodium carbonate and 10wt% sodium nitrate, and finally obtain an aluminum alloy wire.

[0073] Example 7

[0074] The difference from Example 1 is that the pickling process is to use a pickling agent to perform a third spraying of the alkaline-etched billet at 72° C. for 18 seconds, and the pressure of the third spraying is 2 MPa to obtain a pickled billet. The pickling agent is a mixed solution containing 4wt% hydrofluoric acid, 5wt% phosphoric acid, 2.5wt% nitric acid, 1.8wt% sulfuric acid, and 6wt% organic acid malonic acid, and finally an aluminum alloy wire is obtained.

[0075] Example 8

[0076] The difference from Example 1 is that the pickling process is to use a pickling agent to perform a third spraying of the alkaline-etched billet at 65° C. for 25 seconds, and the pressure of the third spraying is 8 MPa to obtain a pickled billet. The pickling agent is a mixed solution containing 1wt% hydrofluoric acid, 15wt% phosphoric acid, 0.5wt% nitric acid, 0.8wt% sulfuric acid, and 2wt% organic acid malonic acid, and finally obtain an aluminum alloy wire.

[0077] Example 9

[0078] The difference from Example 1 is that the coating process is to use the coating liquid to spray the washed billet for the fourth time at 78°C for 19s, and the pressure of the fourth spraying is 6MPa to obtain the coated billet. The coating liquid is a mixed liquid containing 8wt% of the supplementer, 10wt% of the regulator, and 1.2wt% of the corrosion inhibitor, and finally the aluminum alloy wire is obtained.

[0079] Example 10

[0080] The difference from Example 1 is that the coating process is to use the coating liquid to perform a fourth spraying of the washed billet at 55°C for 25s, and the pressure of the fourth spraying is 10MPa to obtain a coated billet. The coating liquid is a mixed liquid containing 5wt% of an extender, 14wt% of a regulator, and 0.2wt% of a corrosion inhibitor, and finally an aluminum alloy wire is obtained.

[0081] Embodiment 11

[0082] The difference from Example 1 is that the intermediate annealing temperature is 440° C., and an aluminum alloy wire is finally obtained.

[0083] Example 12

[0084] The difference from Example 1 is that the sum of the masses of the Fe element and the Cu element is 2%, and the mass ratio of the Fe element to the Cu element is 0.02:1; the sum of the masses of the Mn element and the Cu element is 0.51%, and the mass ratio of the Mn element to the Cu element is 0.1:1, and finally an aluminum alloy wire is obtained.

[0085] Example 13

[0086] The difference from Example 1 is that the sum of the masses of the Fe element and the Cu element is 2%, and the mass ratio of the Fe element to the Cu element is 4:1; the sum of the masses of the Mn element and the Cu element is 0.51%, and the mass ratio of the Mn element to the Cu element is 3:1, and finally an aluminum alloy wire is obtained.

[0087] Comparative Example 1

[0088] The difference from Example 1 is that the surface of the hot-rolled billet is not dissolved, and the aluminum alloy wire is finally obtained.

[0089] Comparative Example 2

[0090] The difference from Example 1 is that the blank after the surface is dissolved is not subjected to alkaline etching and pickling, and the aluminum alloy wire is finally obtained.

[0091] Comparative Example 3

[0092] The difference from Example 1 is that the washed blank is not coated, and an aluminum alloy wire is finally obtained.

[0093] Comparative Example 4

[0094] The difference from Example 1 is that the intermediate annealing temperature is 380° C., and an aluminum alloy wire is finally obtained.

[0095] Comparative Example 5

[0096] The difference from Example 1 is that in step S4, the processing process of step S2 is not repeated on the cold-drawn wire, and finally an aluminum alloy wire is obtained.

[0097] Comparative Example 6

[0098] The difference from Example 1 is that the electrode potential of the hot-rolled billet is -650 mV, and an aluminum alloy wire is finally obtained.

[0099] Test method:

[0100] Electrode potential test: Three-electrode electrochemical workstation, using 3.5% NaCl as the medium, start the test after soaking for 30 minutes.

[0101] Test of surface brightness L and surface brightness color difference △E: Use spectrophotometer for testing.

[0102] Test of average roughness Sa and maximum peak height Sp: Tested using a profilometer.

[0103] Qualification rate test after 85% compression deformation: Tested according to GB / T 3250-2007 and GJB 2055A-2018.

[0104] Corrosion depth test: The aluminum alloy wire was immersed in a mixed solution of 57 g / L NaCl solution and 10 mL / L H2O2 solution at 35°C for 6 h, and the corrosion depth was measured by metallographic observation of the cross-sectional morphology.

[0105] Tests on recrystallization texture content, dislocation density and average grain size: Tests were performed based on EBSD analysis.

[0106] The aluminum alloy wires of the above embodiments and comparative examples were subjected to performance tests, and the test results are shown in Tables 1 and 2.

[0107] Table 1

[0108]

[0109] Table 2

[0110]

[0111] in, Figure 1 is the surface morphology of the aluminum alloy wire in Example 1. Figure 1 It can be seen that the surface color of the aluminum alloy wire is relatively consistent, with no obvious color difference. The overall color is white and bright.

[0112] Figure 2 is the surface roughness diagram of the aluminum alloy wire in Example 1, from Figure 2 It can be seen that the maximum value of the Z axis in the aluminum alloy wire is 1.8, which means that the maximum peak height Sp is 1.8μm, indicating that its roughness is relatively low.

[0113] Figure 3 is the corrosion morphology of the aluminum alloy wire in Example 1. Figure 3 It can be seen that the aluminum alloy wire has no obvious corrosion after immersion, and the corrosion depth is 7μm, indicating that its corrosion resistance is good.

[0114] Figure 4 This is a surface morphology diagram of the aluminum alloy wire in Comparative Example 5. Figure 4 It can be seen that the aluminum alloy wire presents alternating black and white morphology, which are traces of drawing and scratching, and there is obvious surface color difference.

[0115] Figure 5 This is a surface roughness diagram of the aluminum alloy wire in Comparative Example 5. Figure 5 It can be seen that the maximum value of the Z axis in the aluminum alloy wire is 6.3, which means that the maximum peak height Sp is 6.3μm, indicating that its roughness is relatively high.

[0116] Figure 6 This is a corrosion morphology diagram of the aluminum alloy wire in Example 5. Figure 6 It can be seen that after immersion, the aluminum alloy wire shows obvious signs of corrosion, with a corrosion depth of 87μm, indicating that its corrosion resistance is poor.

[0117] In Table 1, the qualified rates of the aluminum alloy wires in the embodiments after 85% compression deformation all reach 100%, indicating that the aluminum alloy wires of the present application do not crack after 85% compression deformation.

[0118] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0119] The present application can avoid the excessive formation of large-sized second phases such as AlCuFe and AlCuMn by controlling the content of each element within the above range, especially the control of Fe, Mn and Cu elements, which is conducive to the reasonable regulation of the electrode potential of the alloy surface layer, thereby making the aluminum alloy wire uniform in structure and having good surface brightness and surface roughness and other properties. At the same time, under the above corrosion test conditions, the corrosion depth of the aluminum alloy wire reaches the above range, so the aluminum alloy wire of the present application also has good corrosion resistance. In summary, the aluminum alloy wire of the present application presents a bright surface, the finished product has excellent surface quality, no additional coating, and no adverse effects on the processing of rear-end fastener parts.

[0120] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An aluminum alloy wire, characterized in that: The aluminum alloy wire comprises the following elements in percentage by mass: 0.1-7.0% of Zn element, 0.2-9.6% of Mg element, 0.1-6.0% of Cu element, 0.01-1.2% of Mn element, 0.1-2.0% of Fe element, 0.1-2.5% of Si element, the total content of unavoidable impurities is ≤0.15%, and the balance is Al element; The surface brightness L of the aluminum alloy wire is greater than 60, and the surface brightness color difference ΔE of the aluminum alloy wire is less than or equal to 0.5; the average roughness Sa of the aluminum alloy wire is less than or equal to 0.4 μm, and the maximum peak height Sp of the aluminum alloy wire is less than or equal to 2.0 μm; The aluminum alloy wire does not crack after being compressed and deformed by 85%; Under the test condition of immersing the aluminum alloy wire in a mixed solution of 57 g / L NaCl solution and 10 mL / L H2O2 solution for 6 hours at a temperature of 35°C, the corrosion depth of the aluminum alloy wire is ≤10 μm; The mass ratio of the Mn element to the Cu element is 0.1-1.6:

1.

2. The aluminum alloy wire according to claim 1, characterized in that The aluminum alloy wire comprises the following elements, in percentage by mass: 0.5-5.5% of Zn element, 0.5-6.0% of Mg element, 0.5-5.0% of Cu element, 0.01-0.8% of Mn element, 0.1-1.5% of Fe element, 0.1-2.0% of Si element, the total content of unavoidable impurities is ≤0.15%, and the balance is Al element; and / or, the mass ratio of the Fe element to the Cu element is 0.02-3:

1.

3. The aluminum alloy wire according to claim 1 or 2, characterized in that: The aluminum alloy wire has a recrystallized texture content of 60-95%, and / or a dislocation density of 0.2×10 14 ~1.0×10 14 m -2 , and / or, the average grain size of the aluminum alloy wire is 5~350μm.

4. A method for preparing the aluminum alloy wire according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Step S1, subjecting raw materials corresponding to the aluminum alloy to batching, smelting, casting, homogenization treatment, hot rough rolling and hot finish rolling in sequence to obtain a hot-rolled billet; Step S2, subjecting the hot-rolled billet to surface dissolution, alkaline etching, pickling, water washing and coating in sequence to obtain a coated billet; Step S3, sequentially performing intermediate annealing and cold drawing on the coated blank to obtain a cold-drawn wire; and Step S4, repeating the processing of steps S2 and S3 on the cold-drawn wire to obtain the aluminum alloy wire; Wherein, the electrode potential of the hot-rolled billet is -770~-1600mV; and the temperature of the intermediate annealing is 400~550°C.

5. The preparation method according to claim 4, characterized in that: In the step S2, the surface dissolution process includes: using a surface dissolving agent to first spray the hot-rolled billet to obtain a billet after surface dissolution; The surface dissolving agent comprises 5-15wt% of a degreasing agent, 2-15wt% of an active agent and 8-12wt% of a penetrant; The temperature of the first spraying is 60-90° C., and / or the pressure of the first spraying is 10-18 MPa; and / or the time of the first spraying is 5-15 s.

6. The preparation method according to claim 5, characterized in that: The degreasing agent is selected from any one or more of boric acid, aminosulfonic acid, borate, sulfate and carbonate, and / or the activating agent is selected from any one or more of alkylphenol polyoxyethylene ether, isomeric decanol polyethylene ether, hexadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide and fatty alcohol polyoxyethylene ether; and / or the penetrant is selected from any one or more of dipropylene glycol, fatty alcohol polyoxyethylene ether and alkyl sodium sulfonate.

7. The preparation method according to claim 5, characterized in that: In the step S2, the alkaline etching process includes: using an alkaline etching agent to perform a second spray wash on the surface-dissolved blank to obtain an alkaline-etched blank; Wherein, the alkaline etching agent comprises 3-10wt% of sodium hydroxide, 6-10wt% of sodium carbonate and 2-8wt% of sodium nitrate; The temperature of the second spraying is 60-90° C., and / or the pressure of the second spraying is 1-10 MPa; and / or the time of the second spraying is 13-25 s.

8. The preparation method according to claim 7, characterized in that: In the step S2, the pickling process includes: using a pickling agent to perform a third spraying on the alkaline-etched blank to obtain a pickled blank; The pickling agent comprises 2-6 wt% of hydrofluoric acid, 2-10 wt% of phosphoric acid, 1-3 wt% of nitric acid, 1-2 wt% of sulfuric acid and 3-16 wt% of organic acid; wherein the organic acid is selected from any one or more of tartaric acid, malonic acid, oxalic acid, malic acid and citric acid; The temperature of the third spraying is 70-90° C., and / or the pressure of the third spraying is 1-5 MPa; and / or the time of the third spraying is 15-20 s.

9. The preparation method according to any one of claims 4 to 8, characterized in that: In the step S2, the coating process includes: using a coating liquid to perform a fourth spray washing on the washed blank to obtain the coated blank; The coating solution includes 7-18 wt% of a supplement, 9-12 wt% of a regulator, and 0.5-2 wt% of a corrosion inhibitor; The temperature of the fourth spraying is 60-90° C., and / or the pressure of the fourth spraying is 1-8 MPa; and / or the time of the fourth spraying is 15-20 s.

10. The preparation method according to claim 9, characterized in that: The supplement is selected from any one or more of fluoroboric acid, ethanol, boric acid and phosphoric acid; and / or, the adjuster is selected from any one or more of nitric acid, hydrofluoric acid and phosphate; and / or, the corrosion inhibitor is selected from any one or more of hexamethylenetetramine, potassium nitrite, sodium gluconate, nitrilotrimethylenephosphonic acid, ethanolamine phosphate and hexadecylamine.

Citation Information

Patent Citations

  • High-strength aluminum alloy wire as well as preparation method and application thereof

    CN115976379A

  • Preparation method for improving surface quality of 1xxx series aluminum alloy

    CN118950959A